Fukuyama’s Interpretation of Tocqueville’s Teaching on the Nature of Aristocracy and Democracy - Nedeljković, Zoran D. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
In this paper, the author chose Fukuyama’s interpretation of Tocqueville’s teaching about the nature of aristocracy and democracy as the subject of his research. He took particular note of Fukuyama’s observation that Tocqueville, through his observations on advantages and shortages of American society, anticipated Nietzsche’s teachings about aristocratic morality, wondering about what was lost after the change of government and whether the spirit of time changed. The unequivocal answer of the French historian and politologist was that the former aristocratic values ​​have been lost. There is no more daintiness in behavior or nobility in social relations, nor are there independence and distrustfulness, which Nietzsche desperately needed to shadow the ideal of the overman. Instead of a complete man we meet a partial man, an individual hiding in a community of equal citizens who can save their freedom only by moving and working in a group, masquerading as members of an increasing number of associations that take on the power and responsibility for the individual’s existence. Tocqueville finds that in the American civic society the relation of trust - mistrust has turned into the relation of debtor - creditor. He examines in which of all the institutions of American democratic society, which did not originate from the revolution, he could perceive a loss of aristocratic values and examines paradoxical situations where from recently matured democracies a new aristocracy emerges.